Pengaruh Latihan Squat Jump Terhadap Kemampuan Jump Service dalam Permainan Bola Voli di SMAN 2 Labuapi - Moh. Ihsan (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
This study aims to determine the effect of squat jump training on jump service in volleyball games for students of SMAN 2 Labuapi. The approach used in this research is the quantitative approach, using the experimental method. The population used in this study was 10 athletes at SMAN 2 Labuapi, and the samples were 10 athletes. The instrument used is the squat jump test. The data is processed using statistical formulas in the form of calculating the average value, standard deviation, and the two-mean test. The data analysis in this study used the t-test at a significant level of 0.05. The results obtained are that there is an effect of Squat Jump training on Jump Service in volleyball games at the SMAN 2 Labuapi club. By testing the t count of 2.92 and t table of 1.86, so there is a significant difference between the data before and after being given treatment.